A PRELIMINARY STUDY ON THE NEED OF WOMEN’S FIQH MODULE AT REHABILITATION CENTRE IN MALAYSIA (SALAM Digest: Syariah and Law Undergraduate Symposium, 2024)
In Malaysia, numerous rehabilitation centres have been established by the government under specific Acts or regulations as part of efforts to rehabilitate delinquent adolescents. Each of these centres operates using different religious modules, which have been developed by experts, experienced professionals, and authoritative bodies. Generally, the modules currently in use provide only a surface-level understanding of women’s fiqh, focusing primarily on Akidah, Ibadah, and Akhlak. According to the latest statistics from the Social Welfare Department in 2021, women are in greater need of protection and rehabilitation than men. The highest incidence involves women who are pregnant out of wedlock, highlighting a lack of religious knowledge. Consequently, this study aims to analyze the necessity of incorporating a women's fiqh module into rehabilitation centres in Malaysia, specifically for women. The methodology employed in this study is qualitative, involving document analysis and a library search. The results of this study are expected to contribute significantly, not only to the centres but also to stakeholders, including Islamic authorities, by advocating for improvements in the care of women trainees. It is hoped that this will enhance the effectiveness of spirituality-related modules in shaping the well-being and empowerment of women trainees.